2010
DOI: 10.1002/acr.20155
|View full text |Cite
|
Sign up to set email alerts
|

Validation of minimal disease activity criteria for psoriatic arthritis using interventional trial data

Abstract: Objective. New criteria for minimal disease activity (MDA) in psoriatic arthritis (PsA) have been developed. The aim is to provide further validation of these criteria using data obtained in interventional trials with infliximab, a drug with proven efficacy in PsA. Methods. The data were obtained from patients in phase II and III infliximab studies of PsA. In both studies, patients with active PsA were treated with infliximab (5 mg/kg) or placebo followed by a period of treatment with infliximab. Between-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 14 publications
5
135
0
12
Order By: Relevance
“…The composite PsA MDA criteria have been preliminarily validated in both observational and interventional trial cohorts 5, 6. Also, it was previously found that MDA might be predicted after 3 months of anti‐tumor necrosis factor (TNF) therapy by factors such as baseline age, CRP level, and function (as assessed by the Bath Ankylosing Spondylitis Functional Index) in a smaller cohort (n = 146) of PsA patients 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The composite PsA MDA criteria have been preliminarily validated in both observational and interventional trial cohorts 5, 6. Also, it was previously found that MDA might be predicted after 3 months of anti‐tumor necrosis factor (TNF) therapy by factors such as baseline age, CRP level, and function (as assessed by the Bath Ankylosing Spondylitis Functional Index) in a smaller cohort (n = 146) of PsA patients 18.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of these post‐hoc analyses, and as validated by Coates and Helliwell 5, MDA was defined as the presence of at least 5 of the following 7 PsA outcome measures: swollen joint count ≤1 of 66 evaluated; tender joint count ≤1 of 68 evaluated; Psoriasis Area and Severity Index (PASI) ≤1 (range 0–72)11; patient pain visual analog scale (VAS) score ≤15 (range 0–100); patient global assessment of disease activity VAS score of ≤20 (range 0–100); Health Assessment Questionnaire disability index (HAQ DI) score ≤0.5 (range 0–3)12, 13; and tender enthesis points ≤1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an improved prognosis was demonstrated in patients who achieved MDA, whether the improvements were a reflection of the disease course or due to treatment regimens could not be determined with the study design. The MDA criteria were subsequently validated using data from the randomized, controlled IMPACT and IMPACT2 trials in which patients received infliximab for the treatment of PsA 16 . In those trials there were statistically significant differences (infliximab vs placebo treatment) in the percentage of patients who achieved MDA at Week 16 (p < 0.0001) and Week 24 (p < 0.001).…”
Section: Rheumatologymentioning
confidence: 99%
“…Patients achieving MDA are more likely to have a better radiologic outcome, because the achievement of sustained MDA (defined as MDA for over 12 months at consecutive clinic visits) was found to reduce progression of radiographic joint damage over a 3-year period [14]. The MDA criteria were used in the TICOPA (Tight Control of PsA) study, the only randomized study to date addressing whether treating to target using a prespecified target can improve outcome in PsA [15].…”
Section: Treat-to-target or Which Target?mentioning
confidence: 99%